Paper based lateral flow biosensor for detection of contaminant and infection / Yew Chee Hong @ Takahiro - Yew, Chee Hong @ Takahiro (2018)
Conventional diagnostic methods for detecting toxicity in water and mosquito-borne infections are very accurate, yet they are expensive to carry out as they require complicated procedures, sophisticated instrumentation and highly-skilled personnel, limiting their application in areas with poor resources. Recently, paper-based sensors, like lateral flow assays (LFA) and paper-based gas sensors have been developed to tackle the limitations of conventional diagnostic methods by leveraging the modifiability, light weight and capillary properties of paper materials. However, paper-based sensors for chemicals still suffer from the need for large instruments and complex circuitry, and the sensitivity of LFA is challenged by the low amount of target in the samples. Therefore, this study aims to develop and enhance the sensitivity of paper-based sensors for diagnostic purposes. A simple lateral flow paper-based capacitive sensor (PCS) was developed for identification and quantification of chemical liquids with the dependence of an easily obtainable cheaper multimeter. The geometry of the sensor and the conditions during application of the sensor were optimized. With an optimized geometry, PCSs, with and without pre-drying conditions, both were able to distinguish small volumes (70 μL) of liquids and quantify solutions, i.e. ethanol-water and nitrate salt solutions based on a capacitance measurement that reflects their dielectric parameters. The developed PCS was able to detect Fe (III) ions up to 1mM, a concentration too low for the naked eye to detect. The sensitivity of a paper-based LFA was enhanced by realizing fluidic control through the induction of coating on the nitrocellulose (NC) membrane with hydrophobic electrospun polycaprolactone (PCL) nanofibres. FESEM and wettability analyses were performed to study the structural morphology and the hydrophobicity of the electrospin-coated NC membrane, respectively. The modified LFA was able to detect 0.5 nM of synthetic Zika virus DNA, a 10-fold of signal enhancement relative to the unmodified LFA. As a proof of concept, the developed PCS and electrospin-coating method demonstrate great potential for sensitive detection of toxicity and infection in paper-based lateral flow diagnostic platforms.